Implementation of performance management in improving quality of work of Lava Cheese employees - Adhine Iadhalia; Fera Uswatun Khasanah; Gita Armelina; Heni Purweny; Satriadi Satriadi (International Journal of Management Research and Economics, 2024)
In a company, the application of maximum performance management must be applied for the sustainability of the company itself, because a company must have effective performance management to achieve predetermined goals, in this study the performance management applied by Lava Cheese to improve employee performance based on 4 stages, namely the planning, implementation, assessment and follow-up stages. The application of performance management implemented by Lava Cheese includes assessing employees, actions taken when problems occur, what matters are taken into consideration. Lava cheese is an F&B restaurant engaged in fast food, this restaurant is located at Jalan Kuantan KM 5 Tanjungpinang, Riau Islands. The purpose of this research is to find out how the implementation of performance management in the Lava Cheese restaurant, this research was conducted using descriptive qualitative methods and with the results of interviews and surveys, the resource persons in this study were lava cheese managers who played an important role in the implementation of performance management at Lava Cheese.